Living Bacteria in Thermoresponsive Gel for Treating Fungal Infections. (6th August 2018) - Lufton, Maayan; Bustan, Or; Eylon, Bat‐hen; Shtifman‐Segal, Ella; Croitoru‐Sadger, Tsuf; Shagan, Alona; Shabtay‐Orbach, Ayelet; Corem‐Salkmon, Enav; Berman, Judith; Nyska, Abraham; Mizrahi, Boaz
Abstract: The leading living bacteria formulations currently available are from a limited list of genera and are generally limited to gastrointestinal tract syndromes. A formulation composed of living Bacillus subtilis incorporated in a thermoresponsive hydrogel that hardens after administration on the skin and continuously produces antifungal agents is described. The ability of the formula to support bacteria growth and its mechanical properties and penetrability through the skin are fine‐tuned by varying the ratio between polymer concentrations and bacterial media. The formula penetrates via the stratum corneum and accumulates in the epidermis without penetrating the inner, dermis layer. In vivo results mirror the results seen in vitro: bacillus formulations completely inhibit candida growth, demonstrating clinical effects comparable to those achieved by ketoconazole. LC‐MS/MS analysis of the bacterial formulation confirms the presence of surfactin, the most powerful biosurfactant that possesses a broad antifungal activity. This platform may enable rational design of novel formulations composed of secreting bacteria inside a responsive, smart, hydrogel—which is the prerequisite for producing a successful drug delivery system. Abstract : A living bacterial formulation based on incorporating gram‐positive bacteria in a bacterial‐supportive formulation is proposed for efficient antifungal treatment. Such a platform offers a safe and clinically effective antifungal therapy as well as great potential to advance the way biologic drugs are administrated with minimal user‐interface.